The Early 1990s Cigarette Price Decrease and Trends in Youth Smoking in Ontario: Where Are We At? - Waller, Bronwen J. (Can J Public Health, 2003)
Background: Youth are especially vulnerable to fluctuations in cigarette price, and both the smuggling increase during the early 1990s and the 1994 tax decrease made purchasing easier for youth. The purpose of this study is to examine the relation between these price decreases, and trends in smoking prevalence and amount smoked among Ontario youth. Methods: Data from the Ontario Student Drug Use Survey were analyzed for trend using: 1) polynomial regression, and 2) discontinuity regression with an “event time” of 1993 to capture effects of both pre-tax cut smuggling and the tax cut. Results: Overall, smoking prevalence decreased from 1977 to 1993, jumped upward at this time, and decreased after 1993. Among daily smokers, mean number of cigarettes smoked daily showed an increase followed by a decrease over the 24 years, and a negative quadratic trend. Trends for subgroups are also reported. Conclusions: These findings suggest that the early 1990s cigarette price decrease may have played a role in increasing youth smoking in Ontario.